Creating Imaginary Role Models for Entrepreneurial Women : A CLA Workshop Exploring Images of the Preferred Future - Fey, Freya (My University, 2023)
Women in entrepreneurship are a growing research topic in multiple fields. Despite the growing interest, women still face multiple barriers and discrimination in entrepreneurship. The aim of this thesis is two-folded: the first aim is to empower entrepreneurial women by investigating their images of the preferred future as a source of inspiration. The second, more implicit aim is to uncover whether futures studies theories and methods can enhance people’s sense of futures agency. This thesis met these twin research aims by establishing preferred images of the future as inspirational role models within the realm of anticipation, enabling an understanding of the power of creating and using these images to change one’s sense of futures agency. The methodology section contributes to achieving the goals by implementing participatory research and designing a CLA workshop for entrepreneurial women in which the participants were able to create their own images of the preferred images, combined with a reflective questionnaire and discussion round. This research produced several key findings: the created images of the preferred future – namely Entrepreneurship 2.0, Mum, the Lioness, Welcome to a Value-Based Society and Princess Charming – are meaningfully inspirational and target important aspects of issues women face in the current social reality. Such encouraging preferred images of the future can serve as beneficial role models for entrepreneurial women. Furthermore, the participatory workshop approach enabled the entrepreneurial women to unconsciously improve their sense of futures agency. The main conclusions drawn from this research were that images of the preferred future indeed serve as role models and that even a short participatory workshop can entail an improved sense of futures agency. This research recommends that participatory research needs further investigation into its purpose to enable participants even when resources are scarce, and its power to motivate participants to consider their anticipatory assumptions and the encountered novelty.
Keywords: Women in entrepreneurship, participatory workshops, Causal Layered Analysis, images of the preferred future, sense of futures agency